2021
DOI: 10.3389/fenvs.2021.706880
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions and Carbon Sinks of an Italian Natural Park

Abstract: Natural parks (NPs) have a primary role in supporting people’s welfare by maintaining natural and cultural resources. Various activities, such as those related to conservation of flora and fauna, forestry, agriculture and livestock, residential, and tourism, coexist within the boundaries of NPs. All these activities may contribute as a source or sink of carbon dioxide and, despite some NPs having started to promote their environmental services, there is currently a lack of information on their carbon footprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Terrestrial habitats are generally a sink for atmospheric carbon sequestration and greenhouse gas flux modulation. Grossi et al [71] proposed a comprehensive methodological approach to both quantitatively and qualitatively estimating emission and sequestration of greenhouse gases by plants and highlighted the potential of green spaces to mitigate climate change impacts. The results of research revealed that highest weakened carbon sequestration occurs in the Zagros Mountains Forest steppe ecosystem, indicating remarkable changes in the ecosystem NPP values, and carbon sequestration and storage decreased owing to the loss of forest cover.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial habitats are generally a sink for atmospheric carbon sequestration and greenhouse gas flux modulation. Grossi et al [71] proposed a comprehensive methodological approach to both quantitatively and qualitatively estimating emission and sequestration of greenhouse gases by plants and highlighted the potential of green spaces to mitigate climate change impacts. The results of research revealed that highest weakened carbon sequestration occurs in the Zagros Mountains Forest steppe ecosystem, indicating remarkable changes in the ecosystem NPP values, and carbon sequestration and storage decreased owing to the loss of forest cover.…”
Section: Discussionmentioning
confidence: 99%
“…Tue et al quantified the carbon storage in the tropical mangrove ecosystem of Mui Ca Mau National Park in Vietnam by measuring trees, roots, fallen sawdust, sediment organic carbon and total depth, as this information can be used to help develop more accurate climate change models and mitigation strategies as well as to effectively reduce emissions from deforestation and degradation (REDD+) schemes [ 13 ]. Grossi et al provided an overall method to quantitatively and qualitatively assess the annual emissions and removal of greenhouse gas (GHG) in the Italian Natural Park, which can help the national major planning strategies to effectively mitigate the greenhouse gas emissions and support the environmental certification process [ 14 ]. Dimobe et al established a research basis for achieving the goals set in the national established contribution and whether an effort helps to maintain or increase the carbon stored in the region by assessing the carbon sink capacity of the national parks.…”
Section: Introductionmentioning
confidence: 99%